Kesesuaian Lahan Untuk Pengembangan Tanaman Sengon (Paraserianthes falcataria) di Desa Wonokerto, Kecamatan Wonosalam, Jombang: Land Suitability For Sengon (Paraserianthes falcataria) Plant Development In Wonokerto Village, Wonosalam District, Jombang - Pamenang, Primaldy; Maroeto; Arifin, Mochamad (Agrocentrum, 2025)
This study evaluated land suitability for sengon (Paraserianthes falcataria) plants by utilizing soil physicochemical parameters and Geographic Information System (GIS) technology. The criteria analyzed included soil pH, organic carbon, texture, Cation Exchange Capacity (CEC), and base saturation. Sampling was conducted purposively in three land use types, namely rice fields, gardens, and dry fields. The analysis results showed that most of the land in the study area was classified as Very Suitable (S1) and Moderately Suitable (S2). The main limiting factor identified was the relatively low soil pH, especially in rice fields. Overall, the soil has a clay texture that is good at storing water and nutrients, and is supported by organic carbon and CEC values ​​​​that are included in the S1 class. Thus, it can be concluded that the general condition of the land has met the criteria to support sengon growth, with recommendations to improve the acidity level (pH) of the soil to achieve optimal productivity.